Concurrent validity of a patient self-administered examination and a clinical examination for femoroacetabular impingement syndrome. Issue 1 (10th October 2019) - Owusu-Akyaw, Kwadwo Adu; Hutyra, Carolyn A; Evanson, Richard J; Cook, Chad E; Reiman, Mike; Mather, Richard C
Abstract : Objective: Telehealth has been established as a viable option for improved access and timeliness of care. Physician-guided patient self-evaluation may improve the viability of telehealth evaluation; however, there are little data evaluating the efficacy of self-administered examination (SAE). This study aims to compare the diagnostic accuracy of a patient SAE to a traditional standardised clinical examination (SCE) for evaluation of femoroacetabular impingement syndrome (FAIS). Methods: 75 patients seeking care for hip-related pain were included for participation. All patients underwent both SAE and SCE and were randomised to the order of the examinations. Diagnostic accuracy statistics were calculated for both examination group for a final diagnosis of FAIS. Mean diagnostic accuracy results for each group were then compared using Mann-Whitney U non-parametric tests. Results: The diagnostic accuracy of individual SAE and SCE manoeuvres varied widely. Both SAE and SCE demonstrated no to moderate change in post-test probability for the diagnosis of FAIS. Although low, SAE demonstrated a statistically greater mean diagnostic accuracy compared with the SCE (53.6% vs 45.5%, p=0.02). Conclusion: Diagnostic accuracy was statistically significantly higher for the self-exam than for the traditional clinical exam although the difference may not be clinically relevant. Although the mean accuracy remains relatively low for both exams, these values are consistent with hip exam for FAIS reported in the literature. Having established the validity of an SAE, future investigations will need to evaluate implementation in a telehealth setting.